Where the wild things are: looking for uncultured Glomeromycota. Issue 1 (19th June 2014) - Ohsowski, Brian M.; Zaitsoff, P. Dylan; Öpik, Maarja; Hart, Miranda M.
Summary: Our knowledge of Glomeromycotan fungi rests largely on studies of cultured isolates. However, these isolates probably comprise one life‐history strategy – ruderal. Consequently, our knowledge of arbuscular mycorrhizal (AM) fungi may be biased towards fungi that occur primarily in disturbed habitats and associate with disturbance‐tolerant host plants. We can expect to see a signal for this in DNA‐based community surveys: human‐impacted habitats and cultivated plants should yield a higher proportion of AM fungal species that have been cultured compared with natural habitats and wild plants. Using the Maarj AM database (a curated open‐access database of Glomeromycotan sequences), we performed a meta‐analysis on studies that described AM fungal communities from a variety of habitats and host plants. We found a greater proportion of cultured AM fungal taxa in human‐impacted habitats. In particular, undisturbed forests and grasslands/savannahs contained significantly fewer cultured taxa than human‐impacted sites. We also found that wild plants hosted fewer cultured fungal taxa than cultivated plants. Our data show that natural communities of AM fungi are composed largely of uncultured taxa, and this is particularly pronounced in natural habitats and wild plants. We are better poised to understand the functioning of AM symbioses associated with cultivated plants and human‐impacted habitats.